2021
DOI: 10.14202/vetworld.2021.847-853
|View full text |Cite
|
Sign up to set email alerts
|

Dietary polyvinyl alcohol and alginate nanofibers ameliorate hyperglycemia by reducing insulin and glucose-metabolizing enzyme levels in rats with streptozotocin-induced diabetes

Abstract: Background and Aim: Dietary management and antidiabetic drugs are used as therapies for diabetic patients worldwide. Alginate nanofibers were developed as a digestible food product that provides sufficient calories. This study aimed to evaluate the effect of polyvinyl alcohol (PVA) and alginate nanofibers on weight gain, blood glucose levels, and insulin and other serum parameters in diabetic rats. Materials and Methods: A total of 24 male Wistar rats were divided into six groups: (C–) Control group, (C+) dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Tissue engineering has proven that scaffold-based cell construction can improve the tendon healing process. 2 Previous studies have shown better histological figures and biomechanical function in tendon defects filled with scaffold and powder coated mesenchymal stem cells taken from bone marrow compared to scaffolds without mesenchymal stem cells. 3 Tendons have several variations and shapes and consist of both intracellular and extracellular matrix components.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering has proven that scaffold-based cell construction can improve the tendon healing process. 2 Previous studies have shown better histological figures and biomechanical function in tendon defects filled with scaffold and powder coated mesenchymal stem cells taken from bone marrow compared to scaffolds without mesenchymal stem cells. 3 Tendons have several variations and shapes and consist of both intracellular and extracellular matrix components.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the T2 group experienced a faster final proliferation phase so the administration of Oregano extract ointment with a 6% concentration was the most effective result in the wound healing process. The final stage of proliferation towards maturation is marked by a decrease in the number of fibroblast cells which regenerate into fibrocyte cells, then the fibroblasts will secrete collagen and form granulation tissue until the wound surface closes (Prestiyanti, 2021;Suryadiningrat et al, 2021). Tannins inhibit the attachment of bacteria to the surface of skin wounds.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, a higher water-holding capacity promotes more thorough defecation, while higher viscosity reduces cholesterol absorption by the small intestine . Alginate nanofibers have been shown to improve obesity and hyperglycemia by alleviating insulin resistance and reducing serum ALT, ALP, GGT, creatinine, TNF-α, and IL-1β content . Similarly, ultrasonic treatment of insoluble dietary fiber derived from garlic straw enhances its cholesterol-binding capacity (58.2%) and oil-holding properties (17.9%), showing potential benefits in reducing the risk of obesity and angiography .…”
Section: Strategies For Enhancing the Biological Activity Of Dietary ...mentioning
confidence: 99%
“…191 Alginate nanofibers have been shown to improve obesity and hyperglycemia by alleviating insulin resistance and reducing serum ALT, ALP, GGT, creatinine, TNF-α, and IL-1β content. 192 Similarly, ultrasonic treatment of insoluble dietary fiber derived from garlic straw enhances its cholesterol-binding capacity (58.2%) and oil-holding properties (17.9%), showing potential benefits in reducing the risk of obesity and angiography. 193 Overall, the reasonable application of a physical modification approach for improving the biological activity of dietary fiber is encouraging.…”
Section: Strategies For Enhancing the Biological Activity Of Dietary ...mentioning
confidence: 99%